Language decline and death in Africa : causes, consequences, and challenges - Batibo, Herman (Multilingual matters (Series), 2005)
The aim of this book is to inform both scholars and the public about the nature and extent of the problem of language decline and death in Africa. It resourcefully traces the main causes and circumstances of language endangerment, the processes and extent of language shift and death, and the consequences of language loss to the continent's rich linguistic and cultural heritage. The book outlines some of the challenges that have emerged out of the situation.